Works done in the field of application of information technologies to libraries. (based on the creation of the technological model of the Azerbaijan University of Architecture and Construction Library) - Salamli, Sevinj Mammad (Technium Social Sciences Journal, 2023)
One of the achievements in the field of education development in recent years is the emergence and development of digital libraries. This term began to be used in the late 80s in foreign publications in connection with the development of Project Gutenberg in 1971. This process is intensively developed and improved to this day. Depending on the level of development of the state (availability of high-speed Internet, financing of institutions, etc.), this process develops at different rates around the world and involves various public and private institutions. Digital libraries have become even more important during the COVID-19 pandemic as researchers and readers have been able to access vast amounts of resources at any time of the day during this challenging period when people have been confined to their homes. To date, the presence of an electronic library in the university has become an indicator of its respectability. There are certain criteria for university libraries, so they must cover scientific, educational and methodological literature in all taught disciplines. The main advantage of digital libraries is the confidence that they will deliver information better than it was in the past. At the same time, the creation and development of electronic libraries encounters a number of problems and difficulties. First of all, at present there is no clear understanding of what an electronic library is, what information systems should be attributed to this class, what are the requirements and evaluation criteria for them. In this article, we will analyze the emergence and development of the digital library, reveal the main obstacles to its development based on the creation of a technological model for the library of the Azerbaijan University of Architecture and Construction and the electronic library of the Mimar Sinan University of Fine Arts in Turkey.